2008
DOI: 10.1109/csmr.2008.4493302
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis and Issue Prediction in Large-Scale Open Source Systems

Abstract: Effort to evolve and maintain a software system is likely to vary depending on the amount and frequency of change requests. This paper proposes to model change requests as time series and to rely on time series mathematical framework to analyze and model them. In particular, this paper focuses on the number of new change requests per KLOC and per unit of time. Time series can have a two-fold application: they can be used to forecast future values and to identify trends. Increasing trends can indicate an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…In all figures we also observe that the further we move the training period to the past the more likely the prediction quality would drop down to almost random (≈ 0.5). This provides some evidence to the statement the further back you go in time the more the prediction deteriorates (Kenmei et al 2008). More formally, from April 2002 to July 2003 the model exhibits a stable good prediction quality.…”
Section: Finding Periods Of Stability and Changementioning
confidence: 91%
“…In all figures we also observe that the further we move the training period to the past the more likely the prediction quality would drop down to almost random (≈ 0.5). This provides some evidence to the statement the further back you go in time the more the prediction deteriorates (Kenmei et al 2008). More formally, from April 2002 to July 2003 the model exhibits a stable good prediction quality.…”
Section: Finding Periods Of Stability and Changementioning
confidence: 91%
“…For Spring they also found that the single best predictor was the number of times a file had been changed, followed by the number of authors of these changes. Kenmei et al [10] collected bi-weekly snapshots over five years for three systems, one of which was Eclipse. From every snapshot they extracted the number of lines of code and identified the number of new change requests, i.e.…”
Section: Related Workmentioning
confidence: 99%
“…Kenmei et al also use ARIMA models for predicting change requests, but build a different model for each of the four open-source systems (including Eclipse) they study [6]. They adopted a sampling policy of aggregating data every two weeks, so that they would have longer time series than if using monthly data.…”
Section: Related Workmentioning
confidence: 99%
“…The LjungBox test confirms that the random walk model is significantly less robust than our prediction model and, therefore, not appropriate. [6], is an ARIMA(5,0,5)(0,0,0). This is clearly the strongest alternative to the model proposed in this paper among those used in this comparison.…”
Section: Hypothesis H3mentioning
confidence: 99%
See 1 more Smart Citation